A simulation study of the effect of target motion on sighting estimates of minke whale population density - Basson, Marinelle (Department of Mathematics and Applied Mathematics, 2016)
Line transect methods used to estimate population density assume stationarity of targets. Violation of this assumption leads to overestimation of the true density. A simulation study based on a hazard-rate model is used to assess the resulting bias. The model is calibrated to generate sighting data resembling real data from minke whale sighting surveys. The procedure currently used to calculate a corrected negative exponential density estimate from sighting data is duplicated using simulated data. The resulting estimates are compared to the true population density determined by the simulation. Results reveal that in the case considered, the method of calculating the g(O) factor (which corrects for the fact that all animals on the trackline are not sighted) leads to a greater degree of overestimation than the effect of target motion at 3 knots. Shortcomings of the model are pointed out and possible improvements suggested. It is also suggested that further research be focused initially on the calculation of the g(O) correction factor rather than on effects of target motion.